Anti-Müllerian Hormone in Fertility Preservation: Clinical and Therapeutic Applications. (June 2019) - Sonigo, Charlotte; Beau, Isabelle; Binart, Nadine; Grynberg, Michael
Anti-Müllerian hormone (AMH) is a member of the transforming growth factor (TGF)-beta family and a key regulator of sexual differentiation and folliculogenesis. While the serum AMH level has been used in reproductive medicine as a biomarker of quantitative ovarian reserve for more than 20 years, new potential therapeutic applications of recombinant AMH are emerging, notably in the field of oncofertility. Indeed, it is well known that chemotherapy, used to treat cancer, induces ovarian follicular depletion and subsequent infertility. Animal models have been used widely to understand the effects of different cytotoxic agents on ovarian function, and several hypotheses regarding chemotherapy gonadotoxicity have been proposed, that is, it might have a direct detrimental effect on the primordial follicles constituting the ovarian reserve and/or on the pool of growing follicles secreting AMH. Recently, a new mechanism of chemotherapy-induced follicular depletion, called the "burn-out effect, " has been proposed. According to this theory, chemotherapeutic agents may lead to a massive growth of dormant follicles which are then destroyed. As AMH is one of the factors regulating the recruitment of primordial follicles from the ovarian reserve, recombinant AMH administration concomitant with chemotherapy might limit follicular depletion, therefore representing a promising option for preserving fertility in women suffering from cancer. This review reports on the potential usefulness of AMH measurement as well as AMH's role as a therapeutic agent in the field of female fertility preservation.